2000
DOI: 10.1177/0148607100024006317
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine‐Driven Inflammatory Response Is Associated with the Hypermetabolism of AIDS Patients with Opportunistic Infections

Abstract: Resting hypermetabolism observed in AIDS patients with concurrent active infections is related to the presence and severity of systemic cytokine-driven inflammatory response, which could reflect the type of secondary infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
15
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…We found that 43.6% of the patients (n ¼ 24) had CRP levels of 0.5 mg/dl or greater, a value considered indicative of an inflammatory condition. A direct association between inflammatory state and REE has been reported in other disease conditions such as rheumatoid arthritis (Roubenoff et al, 1994), acquired immune deficiency syndrome (Garcia-Lorda et al, 2000), sepsis (Chioléro et al, 1997) and pancreatic cancer (Falconer et al, 1994). Recently, our group also demonstrated such relationship in CKD patients not yet on dialysis (Avesani et al, 2004a;Utaka et al, 2005).…”
Section: Discussionsupporting
confidence: 68%
“…We found that 43.6% of the patients (n ¼ 24) had CRP levels of 0.5 mg/dl or greater, a value considered indicative of an inflammatory condition. A direct association between inflammatory state and REE has been reported in other disease conditions such as rheumatoid arthritis (Roubenoff et al, 1994), acquired immune deficiency syndrome (Garcia-Lorda et al, 2000), sepsis (Chioléro et al, 1997) and pancreatic cancer (Falconer et al, 1994). Recently, our group also demonstrated such relationship in CKD patients not yet on dialysis (Avesani et al, 2004a;Utaka et al, 2005).…”
Section: Discussionsupporting
confidence: 68%
“…A predictive value of CRP for REE has previously been reported in cystic fibrosis (39) and AIDS patients (40). More detailed investigations of the role of alternative pathways in this HbSS related inflammation are needed.…”
Section: Discussionmentioning
confidence: 90%
“…The characteristic response to stresses of trauma injury, infection, and other disease, includes hypermetabolism and protein catabolism (3,4,(23)(24) associated with a cytokinedriven inflammatory response in which increased levels of cytokines and acute phase proteins are considered to induce the hypermetabolism. Stable HbSS patients portray many similar characteristics including elevated energy expenditure, protein turnover (1, 2, 25-27), protein catabolism via increased urea production rate (28)(29), increased plasma concentrations of acute phase proteins (8) and leukocytosis (5).…”
Section: Discussionmentioning
confidence: 99%
“…The levels of soluble TNF receptor types I and II, which reflect TNF activity, increase with disease severity but do not correlate with REE in asymptomatic and symptomatic HIV-infected males [71]. Among patients with AIDS and secondary infections, increased REE per kg of FFM correlates with the inflammatory markers C-reactive protein level, erythrocyte sedimentation rate, ferritin level, IL-6 level, and soluble TNF receptor type I level [43]. Of these, C-reactive protein level is an independent predictor of REE per kg of FFM.…”
mentioning
confidence: 97%